2019
DOI: 10.3390/plants8120587
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Common Greenhouse Gas Emissions by the Cyanobiont of the Azolla–Nostoc Symbiosis and Clues as to Nod Factors in Cyanobacteria

Abstract: Azolla is a genus of aquatic ferns that engages in a unique symbiosis with a cyanobiont that is resistant to cultivation. Azolla spp. are earmarked as a possible candidate to mitigate greenhouse gases, in particular, carbon dioxide. That opinion is underlined here in this paper to show the broader impact of Azolla spp. on greenhouse gas mitigation by revealing the enzyme catalogue in the Nostoc cyanobiont to be a poor contributor to climate change. First, regarding carbon assimilation, it was inferred that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…WP_013192178.1 was earlier identified by the first author of this study, using sequence comparison to a nosZ-containing cyanobacterial protein [3]. The comparison between WP_013192178.1 and the nosZ-containing protein yielded ~31.43% identity and ~55% sequence coverage [3]. Note that the assignment of nomenclature was based on computational methods and not wet experiments.…”
Section: Rationale For An In Silico Study Of a Candidate Protein From...mentioning
confidence: 85%
See 1 more Smart Citation
“…WP_013192178.1 was earlier identified by the first author of this study, using sequence comparison to a nosZ-containing cyanobacterial protein [3]. The comparison between WP_013192178.1 and the nosZ-containing protein yielded ~31.43% identity and ~55% sequence coverage [3]. Note that the assignment of nomenclature was based on computational methods and not wet experiments.…”
Section: Rationale For An In Silico Study Of a Candidate Protein From...mentioning
confidence: 85%
“…Before the oxygenation of the ancient world billions of years ago, prokaryotic lifeforms had to contend with nitrous oxide that saw its birth from corona discharge and not as lightning strikes-although there is literature attributing nitrous oxide emanation to streaks of lightning-which anucleated microorganisms reduced using an enzyme designated as nitrous oxide reductase [1]. Nitrous oxide is a greenhouse gas that subsists in the atmosphere for 114 years and is 298-fold more potent than the benchmark gas of carbon dioxide in global warming potential [2,3]. Nitrous oxide reductases are known to be of the same protein fold as cytochrome oxidases (subunit II), the former being the more pre-historical one and the latter evolving from the ancient fossil of a fold, although this is now disputed [4].…”
Section: Introduction-nitrous Oxide Climate Change and Azollamentioning
confidence: 99%
“…Reinforcing our results, it has to be noted that Nostoc genes with homology to nodE had been already detected by Southern blot in previous studies (Rasmussen et al, 1996). In silico studies in Nostoc have recently identified two ORFs encoding putative homologs of Rhizobium NodB and NodC proteins (Gunawardana, 2019). Rhizobial NFs are induced by flavonoids derived from prospective plant hosts (Mus et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A newer paradigm is presented by Azolla due to the plant's potential as a voracious carbon sink-the Rubisco Carboxylase is the most common enzyme in plants -, which can be utilized 2 Bioinformatics and Biology Insights in abundance due to the strong nitrogen fixation performed by the cyanobiont. 7 I showed in an earlier publication that Trichormus-Azolla symbiosis is a sound future bio-technological ally in a prospective "field-based" setting, due to the absence of nitrous oxide and methane emitting enzymes in the cyanobiont's proteome. 7 A third benefit that can be reaped from Azolla, is its potent ability to quench harmful heavy metals such as lead, chromium and to a lesser extent cadmium.…”
Section: Introductionmentioning
confidence: 99%
“… 7 I showed in an earlier publication that Trichormus-Azolla symbiosis is a sound future bio-technological ally in a prospective “field-based” setting, due to the absence of nitrous oxide and methane emitting enzymes in the cyanobiont’s proteome. 7 A third benefit that can be reaped from Azolla, is its potent ability to quench harmful heavy metals such as lead, chromium and to a lesser extent cadmium. 8 Again, phytoremediation is dependent on proteins such as “sequestering” metallothioneins, and therefore, nitrogen fixation by the cyanobiont, once again, is of strong importance.…”
Section: Introductionmentioning
confidence: 99%